Analysis of triacylglycerols in fat body of bumblebees by chromatographic methods - Cvacka, Josef; Hovorka, Oldrich; Jiros, Pavel; Kindl, Jirí; Stránský, Karel; Valterová, Irena (Journal of chromatography. A, 2006)
Triacylglycerols (TAGs) from the fat body of several bumblebee species (Bombus lucorum, B. terrestris, B. lapidarius, B. hypnorum, B. hortorum, and B. confusus) were studied using chromatographic techniques. Semi-preparative thin-layer chromatography was used to isolate the TAGs from the tissue extract. Gas chromatography (GC) enabled us to identify the fatty acids (FAs) that form bumblebee TAGs and to quantify their relative proportions. The TAGs were subsequently analysed by high-performance liquid chromatography-atmospheric pressure chemical ionisation mass spectrometry. Two chromatographic systems, including non-aqueous reversed-phase chromatography and silver ion chromatography on cation exchange resin in silver (I) ionic form, were optimised and their performance compared. The most abundant fatty acids in bumblebees TAGs contained 18 or 16 carbon atoms; oleic acid predominated in most samples. TAGs were found to be a complex mixture of isomers; some of them, e.g. OLnO, PLnO, PoPoO, PoPoP, POO, or OOO (where Po is palmitoleic, P is palmitic, Ln is linolenic, and O is oleic acid) were abundant in particular species. The composition of both FAs and TAGs was found to be species-specific. Only minor differences were found among specimens of the same species.
Keywords: chromatografie na tenké vrstvě; Chromatography, High Pressure Liquid; tukové těleso; atmosférický tlak; Chromatography, Thin Layer; Atmospheric Pressure; Fat Body; Triglycerides; Animals; triglyceridy; Chromatography, Gas; chromatografie plynová; Bees; zvířata; vysokoúčinná kapalinová chromatografie; včely